DAMPAK HIPNOTERAPI DALAM MENGELOLA KADAR GULA DARAH DAN KUALITAS HIDUP PENDERITA DIABETES MELITUS TIPE II DI DENPASAR SELATAN - Gloria Margaret Wulang; Ni Made Ayu Sukma Widyandari; I Made Rai Mahardika (LPPM STIKES Mataram, 2025)
Background: Diabetes Mellitus Type II is a chronic condition that requires long-term management. One of the main challenges in diabetic patients is unstable blood glucose levels. As a complementary approach, hypnotherapy has been considered to help regulate blood glucose and improve quality of life in patients with DM Type II. Objective: This study aimed to evaluate the effect of hypnotherapy on blood glucose levels and quality of life in patients with Diabetes Mellitus Type II. Methods: A pre-experimental design with a one-group pretest-posttest approach was used. A total of 9 participants were selected using purposive sampling. Blood glucose data were analyzed using paired t-test, and quality of life was assessed using the Wilcoxon Signed Rank Test. Results: The average random blood glucose level before hypnotherapy was 174.56 mg/dL and decreased to 137.89 mg/dL after the intervention. The paired t-test showed a significant effect of hypnotherapy on blood glucose levels (p 0.006). The Wilcoxon test revealed significant improvements across all quality of life domains: physical (p 0.011), psychological (p 0.008), social relationships (p 0.009), and environment (p 0.015). Conclusion: Hypnotherapy significantly reduced blood glucose levels and improved quality of life. It may serve as a complementary therapy in holistic nursing care.